Cardiac autonomic function in healthy young smokers. (January 2015) - Erdem, Alim; Ayhan, Suzi Selim; Öztürk, Serkan; Özlü, Mehmet Fatih; Alcelik, Aytekin; Sahin, Safak; Tosun, Mehmet; Erdem, Fatma Hizal; Gumustekin, Kenan; Yazici, Mehmet
The present study examined the heart rate turbulence (HRT) and heart rate variability (HRV) parameters in healthy young smokers (<40 years) to assess the effects of smoking on cardiac autonomic function. The study included 75 smokers with a history of habitual smoking for at least 1 year (41 males and 34 females; mean age, 29.3 ± 7.3 years) and 30 nonsmokers (hospital staff; 16 males and 14 females; mean age, 29.0 ± 6.1 years). Addiction to smoking was evaluated using the modified Fagerström test for nicotine-dependence index (NDI). HRT, HRV, basic clinical and echocardiographic, and Holter test parameters were compared between groups. No significant differences between the two groups were found in the basic clinical and echocardiographic variables. Turbulence onset (TO) was significantly higher in the smoking group than in the controls, and turbulence slope was significantly lower in the smokers, than in the controls ( p < 0.05). Standard deviation of all normal-to-normal (NN) interval index (SDNNI) was the only HRV parameter that was significantly different between the smoking and control groups ( p < 0.05). The NDI was positively correlated with the TO ( p < 0.05). Smoking impairs the baroregulatory function in healthy young smokers, particularly the HRT parameters and SDNNI. Our findings highlight the importance of complete smoking cessation.